ESTUDIOS INTERNACIONALES EN AMERICA LATINA. EXPERIENCIAS Y DESAFIOS - Tomassini, Luciano (2015)
One of the main challenges facing internationalstudies in Latin America is the clarificationof issues related to global economic systems;which must adapt to new realities thatwill allow developing countries to formulate astrategy more lucid and active that today’s internationalintegration because over the yearsthe outer inclusion of Latin American countriesplayed an important role in their developmentprocesses.